2010
DOI: 10.1289/ehp.1002115
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Lighting as a Vector Attractant and Cause of Disease Diffusion

Abstract: BackgroundTraditionally, epidemiologists have considered electrification to be a positive factor. In fact, electrification and plumbing are typical initiatives that represent the integration of an isolated population into modern society, ensuring the control of pathogens and promoting public health. Nonetheless, electrification is always accompanied by night lighting that attracts insect vectors and changes people’s behavior. Although this may lead to new modes of infection and increased transmission of insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 38 publications
0
58
0
2
Order By: Relevance
“…There are several studies showing that mosquitoes are attracted to light and that malaria vectors are captured using light traps (Barghini and de Medeiros, 2010). This suggests that the Yamamoto et al (2010), who found how households living in Burkina Faso in electrified houses are recorded to have higher occurrence of malaria.…”
Section: Vector Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies showing that mosquitoes are attracted to light and that malaria vectors are captured using light traps (Barghini and de Medeiros, 2010). This suggests that the Yamamoto et al (2010), who found how households living in Burkina Faso in electrified houses are recorded to have higher occurrence of malaria.…”
Section: Vector Densitymentioning
confidence: 99%
“…The changes electrification may bring in someone's life can be multiple, may go in different directions and are very likely to be extremely difficult to disentangle; for what concerns the (Barghini and de Medeiros, 2010). Other changes include social interactions and sport activities, which can now take place outside the dwelling and in the evening with artificial light and which see as main actors especially men and male children (Winther, 2011).…”
Section: Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that mosquitoes are attracted to light (Barghini and de Medeiros, 2010;Barret et al, 1973;Barret et al, 1974), and malaria vectors are captured using 1 In contrast, the relation between access to electricity and the occurrence of Chagas disease and leishmaniasis, has been studied. Chagas disease is commonly transmitted to humans and other mammals by an insect vector while leishmaniasis is a disease caused by protozoan parasites that belong to the genus Leishmania and is transmitted by the bite of certain species of sand fly.…”
Section: Vector Densitymentioning
confidence: 99%
“…Chagas disease is commonly transmitted to humans and other mammals by an insect vector while leishmaniasis is a disease caused by protozoan parasites that belong to the genus Leishmania and is transmitted by the bite of certain species of sand fly. The occurrence of these two types of disease has been proven to increase in electrified areas (Barghini and de Medeiros, 2010). suction light traps with heat or carbon dioxide bait (Jawara et al, 2008;Lee et al, 2009;Suárez-Mutis et al 2009;Tirados at al., 2006).…”
Section: Vector Densitymentioning
confidence: 99%